The Effectiveness of Medical Disaster Emergency Kits Compared to Midwife Kits for Midwife Preparedness in Facing Disasters in Disaster-Prone Areas - Nurul Maulani; Rismayani Rismayani; Entan Afriannisyah (Babali Nursing Research, 2024)
Introduction: Every country needs preparation to face disasters especially for Indonesia which is in the ring of fire, an active volcano cluster. In an emergency to provide first aid, the Midwife can perform health services outside her authority according to her competence. First aid aims to save the client's life or circumstances that threaten the client's life. Medical disaster preparation kits compared to midwife kits for midwife preparedness in dealing with disasters in disaster prone areas in UPT Puskesmas Kandang MasBengkulu City in 2023.